2006
DOI: 10.1093/europace/euj045
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effect of ajmaline in a patient with Brugada syndrome

Abstract: In our patient, the double localization of the typical Brugada-pattern and the paradoxical effect of ajmaline on the ECG abnormalities confirmed the possibility of a phenotype heterogeneity in the Brugada syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Similar patients have also been previously described in case reports relating "abnormal J-wave," however, without establishing the link with early repolarization syndrome or using a control population (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The arrhythmogenicity of this syndrome is thought to be related to heterogeneity of action potentials (spike and dome morphology in epicardial tissue) across the ventricular wall at the end of phase 1.…”
Section: Discussionsupporting
confidence: 69%
“…Similar patients have also been previously described in case reports relating "abnormal J-wave," however, without establishing the link with early repolarization syndrome or using a control population (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The arrhythmogenicity of this syndrome is thought to be related to heterogeneity of action potentials (spike and dome morphology in epicardial tissue) across the ventricular wall at the end of phase 1.…”
Section: Discussionsupporting
confidence: 69%
“…It has been known that the epicardial action potential notch is the result of the balance between three different currents: I Na , I to and I CaL [19]. Theoretically, a reduction in I Na or I CaL or an increase in I to and/or any other potassium current may cause the changes of the configuration of the action potential notch [19,20] that leads to J-point elevation on the ECG. In the general concept, glucose induces insulin secretion.…”
Section: Brugada Syndrome and Carbohydrate Metabolismmentioning
confidence: 99%
“…In the general concept, glucose induces insulin secretion. From many previous studies, insulin has been shown to cause hyperpolarization of membrane potential by activation of the Na + and K + pump [20,21], which activated outward current during the plateau phase of action potential. Therefore, it tends to promote outward current.…”
Section: Brugada Syndrome and Carbohydrate Metabolismmentioning
confidence: 99%